SYSTEM OF MIGRATION IMAGES CREATED BY LUKMAN BURIKHAN - Ruziyeva Ugilnor Egamberdiyevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the skills of well-known artist Luke Borixon based on his stories, such as "People in the Heat," "The Mystery Teacher," "The Young Man Who Sees Hezran," as well as "Anxiety From the Desert," and "The Tumor in the Vineyard."